Effect of chronic exposure to aluminium on isoform expression and activity of rat (Na+/K+)ATPase - Silva, V. S. (2012)
The ability of aluminum to inhibit the (Na+/K+)ATPase activity has been observed by several investigators. The (Na+/K+)ATPase is characterized by a complex molecular heterogeneity that results from the expression and differential association of multiple isoforms of both catalytic (alpha) and regulatory (beta) subunits. For instance, three main alpha (alpha(1), alpha(2) and alpha(3)) and three beta (beta(1), beta(2) and beta(3)) subunit isoforms exist in vertebrate nervous tissue, whereas only alpha(1) and beta(1) have been identified in kidney. However, no studies have focused on determining the change in (Na+/K+)ATPase isoforms caused by chronic exposure to aluminum and its relation with aluminum toxicity. In this study, adult male Wistar rats were submitted to chronic dietary AlCl3 exposure (0.03 g/day of AlCl3 for 4 months), and the activity and protein expression of (Na+/K+)ATPase isozymes were studied in brain cortex synaptosomes and in kidney homogenates. The intracellular levels of adenine nucleotides, plasma membrane integrity, and aluminum accumulation were also studied in brain synaptosomes. Aluminum accumulation upon chronic dietary AlCl3 administration significantly decreased the (Na+/K+)ATPase activity measured in the presence of nonlimiting Mg-ATP concentrations, without compromising protein expression of alpha-subunit isoforms in brain and kidney. Aluminum-induced synaptosomal (Na+/K+)ATPase inhibition was due to a reduction in the activity of isozymes containing alpha(1)-alpha(2) and alpha(3)-subunits. The onset of enzyme inhibition was accompanied by a decrease of the (Na+/K+)ATPase sensitivity to submicromolar concentrations of ouabain, and it preceded major damage in plasma membrane integrity and energy supply, as revealed by the analysis of lactate dehydrogenase leakage and endogenous adenine nucleotides. The data suggest that, during chronic dietary exposure to AlCl3, brain (Na+/K+)ATPase activity drops, even if no significant alterations of catalytic subunit protein expression, cellular energy depletion, and changes in cell membrane integrity are observed. Implications regarding underlying mechanisms of aluminum neurotoxicity are discussed.